An economic study of fry production systems in Northeast Thailand - Purba, Sirman; Waibel, Hermann; Little, David C.; Demaine, Harvey; Australian Government (Bangkok : Asian Institute of Technology, 1990)
The objective of the study is to describe the economic performance of freshwater fish seed hatcheries, to describe the variability among the fry producers and to find out input output relationship . The market s hare of the small, medium, and large private and government hatcheries will also be described . A cross-sectional survey was conducted covering 8 provinces in Northeast Thailand and a total of 67 private hatcheries. The operator of small , medium and large hatcheries were interviewed u sing an open type of questionnaire to obtain the data on economic performance and productivity. The results showed that small hatcheries supplied 7% fry to t he market, the medium and the large supplied 27% a nd 62% respectively, while the government hatcheries supplied only 4% of freshwater fish seed to the market. There are 5 factors that can be used to describe the variability among the private hatcheries which are size of the hatcheries, access to water, location, market dimension and experience, and it was found out that size of the hatcheries is the most responsible factors in explaining the variability among the fry producers. The result indicated that, as the farm size increases the productivity is also increased. Ten types of input variables . have been identified, out of 10 only 3 input variables which are labor, manure, and energy, have significant effect in explaining the output. The efficiency of using input specific to location and farm size can be computed by using the Cobb- Douglas types of function.
A thesis submitted in partial fulfilment of the requirements of the degree of Master of Science, School of Environment, and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Fish hatcheries -- Thailand, Northeastern